A resilience perspective on healthcare personnels' experiences of managing the COVID-19 pandemic: a qualitative study in Norwegian nursing homes and home care services - Malin Knutsen Glette; David W. Bates; Patricia C. Dykes; Siri Wiig; Tone Kringeland (BMC, 2023)
Abstract Background The COVID-19 pandemic led to new and unfamiliar changes in healthcare services globally. Most COVID-19 patients were cared for in primary healthcare services, demanding major adjustments and adaptations in care delivery. Research addressing how rural primary healthcare services coped during the COVID-19 pandemic, and the possible learning potential originating from the pandemic is limited. The aim of this study was to assess how primary healthcare personnel (PHCP) working in rural areas experienced the work situation during the COVID-19 outbreak, and how adaptations to changes induced by the pandemic were handled in nursing homes and home care services. Method This study was conducted as an explorative qualitative study. Four municipalities with affiliated nursing homes and homecare services were included in the study. We conducted focus group interviews with primary healthcare personnel working in rural nursing homes and homecare services in western Norway. The included PHCP were 16 nurses, 7 assistant nurses and 2 assistants. Interviews were audio recorded, transcribed and analyzed using thematic analysis. Results The analysis resulted in three main themes and 16 subthemes describing PHCP experience of the work situation during the COVID-19 pandemic, and how they adapted to the changes and challenges induced by the pandemic. The main themes were: "PHCP demonstrated high adaptive capacity while being put to the test", "Adapting to organizational measures, with varying degree of success" and "Safeguarding the patient's safety and quality of care, but at certain costs". Conclusion This study demonstrated PHCPs major adaptive capacity in response to the challenges and changes induced by the covid-19 pandemic, while working under varying organizational conditions. Many adaptations where long-term solutions improving healthcare delivery, others where short-term solutions forced by inadequate management, governance, or a lack of leadership. Overall, the findings demonstrated the need for all parts of the system to engage in building resilient healthcare services. More research investigating this learning potential, particularly in primary healthcare services, is needed.